Nutritional composition an in situ digestibility of the industrial waste of jasmine tea - Vasquez-Sarabia, Fredy; Robles-Estrada, Juan Carlos; Portillo-Loera, Jesús José; Félix-Bernal, José Adrián; Mejía-Delgadillo, Mario Alejandro; Emus-Medina, Alexis; Sánchez-Pérez, Jaime Noé; Rodríguez-Millán, Jesús; Dávila-Ramos, Horacio (Ecosistemas y Recursos Agropecuarios, 2023)
The objective was to determine the nutritional composition and in situ digestibility of the industrial residue of jasmine tea. Proximal chemical analysis, neutral detergent fiber (NDF) and acid (ADF), metabolizable energy (ME), net maintenance (NEm) and gain (NEg) and tannins, digestibility in situ and degradation kinetics were determined during 0, 3, 6, 12, 18, 24, 36, 48, and 72 h. 20.19% CP, 30.5% CF, 65.61% NDF, 49.01% ADF 1.47 mg g−1 and condensed tannins and 3.21 mg g−1 of hydrolyzables, 2.04 Mcal kg−1 ME, 1.19 Mcal kg−1 ENm and 0.74 Mcal kg−1 NEg were observed. The DM degradation was 50.63% at 72 h, CP showed 17.5% degradation, the degradation kinetics parameters for DM were a = 4.73, b = 48.66 and c = 0.05. It is concluded that the jasmine tea residue is a viable option as a source of fiber in the ruminant diet